Copper responsive Leucoderma in buffaloes - SINGH, RAJIV; RANDHAWA, S S (The Indian Journal of Animal Sciences, 2011)
Buffaloes from organized dairy farm showing achrolllatrichia along with the leucodernla over ventral abdolninal region were selected for the study. HaelnatologicaI parameters along with trace mineral status of the plasma and hair samples were analyzed. Secondary copper deficiency due to elevated level of molybdenum was attributed to be the cause behind the condition. Animals responded to the repeated administration of injectable copper glycinate at intervals of 45 days and 90 days. Â